Website Prototype Design Animation Study Program Based Content Management System Wordpress - Charles De Haan (Jurnal Mantik, 2022)
The availability of information through information and communication technology (ICT) in the world of education is not only supported in operations but has become a necessity and an obligation that must be implemented. One of the application products on the internet that utilizes the development of communication and information technology is a website application. The problem of the lack of information from the main website for animation study program students, plus the Covid-19 pandemic which requires online lectures, causes direct communication and submission of data or documents from study program management to students will experience several problems. We need a website that can bridge the information needs. the most possible way, and can quickly be developed is to use a Web Content Management System. The website is developed in an initial form or often called a prototype, by submitting a questionnaire to prospective website users. The goal is to obtain an overview of what information should be on the website. The results of this study are in the form of a website prototype for an animation study program that is relevant to the needs of users, namely lecturers, students, and the general public.